Fathers' mental health in the postnatal and early childhood period: Results from the Longitudinal Study of Australian Children - D'Esposito, F; Cooklin, A R; Wade, C; Nicholson, J; Lucas, N; Mensah, F; Christensen, D; Giallo, R (My University, 2011)
Much is known about maternal mental health in the postnatal and early childhood period, but research into fathers mental health during this life-stage has been slower to emerge. The need for a better understanding of fathers mental health during the early parenting years is becoming increasingly important given research highlighting the contribution of fathers mental health to the development and wellbeing of children. Therefore, the first aim of the paper was to report on the mental health of a large nationally representative sample of Australian fathers participating in the Longitudinal Study of Australian Children (LSAC) at three time points up to five years post-birth (N=2079-3471). The second aim of the paper was to examine a range of socio-demographic and contextual factors associated with mental health in the first year postpartum. Approximately nine percent (9%) of fathers reported psychological distress during the postnatal period. Of these, 52.9 percent also reported continued distress at a similar level or worse over time. Risk factors for postnatal psychological distress were poor job quality, poor relationship quality, maternal psychological distress, having a partner in a more prestigious occupation and low parental self-efficacy. These findings provide important insights to inform the assessment and identification of fathers at risk of mental health difficulties in postnatal period. There are also important social policy implications related to workplace entitlements and
Keywords: Health -- Mental; Gender -- Male; Families -- Fathers; Families and relationships; Gender; Health and wellbeing; Health; Families; Gender; Male; Fathers; Mental; Health and wellbeing; Families and relationships; Gender